A rock is thrown upward from a bridge into a river below. The function f(t)=−16t2+44t+138 determines the height of the rock above the surfac

Question

A rock is thrown upward from a bridge into a river below. The function f(t)=−16t2+44t+138 determines the height of the rock above the surface of the water (in feet) in terms of the number of seconds t since the rock was thrown. g

in progress 0
Mít Mít 6 months 2021-08-22T05:35:11+00:00 1 Answers 3 views 0

Answers ( )

    0
    2021-08-22T05:36:25+00:00

    Answer:

    a) 138 ft

    b) 4.62 s

    c) 1.375 s

    d) 168.25 ft

    Explanation:

    The height of a rock (thrown from the top of a bridge) above the level of water surface as it varies with time when thrown is given in the question as

    h = f(t) = -16t² + 44t + 138

    with t in seconds, and h in feet

    a) The bridge’s height above the water.

    At t=0 s, the rock is at the level of the Bridge’s height.

    At t = 0,

    h = 0 + 0 + 138 = 138 ft

    b) How many seconds after being thrown does the rock hit the water?

    The rock hits the water surface when h = 0 ft. Solving,

    h = f(t) = -16t² + 44t + 138 = 0

    -16t² + 44t + 138 = 0

    Solving this quadratic equation,

    t = 4.62 s or t = -1.87 s

    Since time cannot be negative,

    t = 4.62 s

    c) How many seconds after being thrown does the rock reach its maximum height above the water?

    At maximum height or at the maximum of any function, the derivative of that function with respect to the independent variable is equal to 0.

    At maximum height,

    (dh/dt) = f'(t) = (df/dt) = 0

    h = f(t) = -16t² + 44t + 138

    (dh/dt) = (df/dt) = -32t + 44 = 0

    32t = 44

    t = (44/32)

    t = 1.375 s

    d) What is the rock’s maximum height above the water?

    The maximum height occurs at t = 1.375 s,

    Substituting this for t in the height equation,

    h = f(t) = -16t² + 44t + 138

    At t = 1.375 s, h = maximum height = H

    H = f(1.375) = -16(1.375²) + 44(1.375) + 138

    H = 168.25 ft

    Hope this Helps!!!

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )